Performance enhancement of adaptive cluster formation and routing protocols in wireless networks - Khalaf, Osamah Ibrahem (2017)
Quality of service (QoS) in Mobile Ad hoc Networks (MANET) has been an interesting research field. The main challenges like packet loss, congestion, multipath fading and link failure, have to be handled wisely. These challenges happen due to several factors like interference, noise, impairments at the physical and network layer, etc. This thesis describes an analysis on the effect of these challenges on the perceived video quality over MANET which is considered the important network in many studies. An enhanced algorithm has been suggested to improve the video quality using routing algorithm which is used to transfer the data packets with minimum number of errors. The impacts of many parameters such as routing protocols, wireless propagation type and encoded video format, on the perceived video quality have been studied. Moreover, the effect of routing protocol and the wireless channel propagation standards on the quality of the received video have been analysed. Layer description coding (LDC), which divides the video frames into the base layer (BL) and enhanced layer (EL), is used to encode and decode the original video. BL can be decoded to construct the original video with basic quality and EL is used to improve the quality of BL. An enhanced routing protocol, which is used to route the BL video packets, namely the improved video transmission protocol (IVRP) was proposed. It is proven can reduce the link failure problem and deliver the video packet in a high quality. The routing discovery process is divided into two stages: intra-routing and inter-routing discovery. The inter- routing corresponds to routing between two sets and it uses the global positioning system (GPS) to obtain location information for each node. For EL video packets, an enhanced routing algorithm was proposed to route the Enhance Layer (EL) packets, namely, Energy Sensible and Route Stability Based Routing Protocol (ESRSBRP) which is used over Mobile network. ESRSBRP selects the highly stable route in term of energy as well as mobility of nodes for the individual data transmission between the source and destination. An enhanced algorithm which is used to improve the video quality was proposed, namely, Effective Broadcast Control Routing algorithm (EBCRA). EBCRA solves the issue of redundant re-transmission of RREQ packet and propose a routing algorithm that deal with the broadcast storm problem which is widely practiced in MANET routing protocol. A model for MANET has been simulated, with various scenarios. The effects of changes in movement (speed), number of sent packets and node density (number of nodes), on the quality of the transmitted video quality have been measured. The IVRP, EBCRA and ESRSBRP performance have been compared with the other routing algorithms. The efficiency and scalability of the proposed algorithms are measured based on different performance metrics, namely: throughput, packet delivery ratio, end to end delay, the number of dropped packets and normalized control overhead. The simulation results have shown that these algorithms can increase the throughput and packet delivery ratio. Furthermore, the end to end delay, number of dropped packets, and normalized control overhead has been reduced, as reflected significantly in the video transmission quality.